Videos in Teaching Listening: A Systematic Literature Review - Marisatul Khasanah (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this study was to evaluate at articles published between 2017 and 2022 that explored the benefits and impact of using video-based learning in the classroom to teach listening. It was considered as a Systematic Literature Review. Data were obtained from ERIC as an online journal database which served a number of reputable journals. They were gathered and analyzed through a systematic examination covering four phases, such as identification, screening, eligibility, and exclusion. In the first phase, 132 articles were obtained however at the last after filtering process, there were only 5 articles remaining. Actually, most of the sources stated that videos play its roles well in enhancing students’ listening skills. Yet, another innovation in using videos in teaching listening were really expected to be investigated for future studies.